Benefit of angiographic spontaneous reperfusion in STEMI: does it extend to diabetic patients?. Issue 16 (15th May 2009) - Bainey, K R; Fu, Y; Granger, C B; Hamm, C W; Holmes, D R; O'Neill, W W; Seabra-Gomes, R; Pfisterer, M E; Van de Werf, F; Armstrong, P W; ,
Abstract : Background: Spontaneous reperfusion (SR) in ST elevation myocardial infarction (STEMI) improves clinical outcome, yet its incidence and impact among diabetic patients is unclear. Objective: To carry out a systematic analysis of SR in the diabetic cohort of a large primary percutaneous coronary intervention (PCI)-treated population with STEMI. Methods and results: 4944 patients (15.5% diabetic) undergoing primary PCI in the APEX AMI study were evaluated. SR defined as pre-PCI Thrombolysis in Myocardial Infarction (TIMI) 3 flow occurred in 11.5% of patients; it was more common in non-diabetic (11.9%) than in diabetic patients (9.2%) (p = 0.028). Patients with SR versus no SR had improved post-PCI TIMI 3 flow: in non-diabetic patients (99.8% vs 90.3%, p<0.001) and in diabetic patients (98.6% vs 84.9%, p<0.001). Non-diabetic patients with SR showed a significant improvement in 90-day death/shock/congestive heart failure (CHF) compared with those without SR: 4.4% versus 8.9% (p = 0.001), respectively. The composite outcome in diabetic patients with versus without SR was 10.0% versus 14.9% (p = 0.270), respectively. When outcomes were examined according to tertiles of baseline blood glucose, both non-diabetic and diabetic patients with normoglycaemia showed higher SR rates (15.5%, 10.3%, 7.3% for non-diabetic patients, p<0.001; 17.4%, 7.2%, 9.1% for diabetic patients, p = 0.132), greater ST resolution (55.4%, 52.6%, 49.7% for non-diabetic patients, p = 0.030; 50%, 46.4%, 39.1% for diabetic patients, p = 0.179), and improved 90-day death/shock/CHF (5.2%, 8.3%, 14% for non-diabetic patients p<0.001; 8.7%, 4.2%, 15.8% for diabetic patients, p = 0.006). Conclusions: These data indicate that SR is less common in diabetic patients with STEMI. Diabetic patients without SR have worse post-PCI epicardial patency, which contributes to adverse outcomes. Diabetic patients with normal baseline blood glucose and SR have enhanced epicardial flow after PCI and improved prognosis.